2024
DOI: 10.1093/jscr/rjae198
|View full text |Cite
|
Sign up to set email alerts
|

Management of ossifying fibroma of the bone of the maxilla: a case report and review of the literature

Kanankira A Nnko,
Raphael T Pima,
Sosthenes Damas
et al.

Abstract: Ossifying fibroma (OF) is a slow-growing benign fibro-osseous neoplasm. It is mostly odontogenic in origin, and it arises in the jaws, particularly the mandible. OF is characterized by the production of bone and cementum-like calcifications in a fibrous stroma. OF reports of the bone of the maxilla are uncommon. Diagnosing OF can be challenging due to the considerable overlap of clinico-pathological characteristics with those of other neoplasms. Herein, the authors describe a case report OF in a 26-year-old ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…Similar to their results, ossifying fibroma was the most commonly reported fibro-osseous lesion in our study. In a systematic review by Kalmegh et al, it was found that fibrous dysplasia contributes to 2.5% of all bone tumors and 7% of benign bone tumors, stemming from congenital, metabolic, and genetic anomalies [15][16][17]. Another study by Akinyamoju et al aimed to assess the utility of a predictive histologic index in identifying malignant changes in jaw fibro-osseous lesions, utilizing a retrospective analysis of hematoxylin and eosin (H&E) slides and archival records of fibrous dysplasia and ossifying fibroma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to their results, ossifying fibroma was the most commonly reported fibro-osseous lesion in our study. In a systematic review by Kalmegh et al, it was found that fibrous dysplasia contributes to 2.5% of all bone tumors and 7% of benign bone tumors, stemming from congenital, metabolic, and genetic anomalies [15][16][17]. Another study by Akinyamoju et al aimed to assess the utility of a predictive histologic index in identifying malignant changes in jaw fibro-osseous lesions, utilizing a retrospective analysis of hematoxylin and eosin (H&E) slides and archival records of fibrous dysplasia and ossifying fibroma cases.…”
Section: Discussionmentioning
confidence: 99%
“…A capacidade de realizar simulações virtuais de procedimentos cirúrgicos antes da intervenção real representa um avanço significativo na prática médica, oferecendo aos profissionais uma visão detalhada e tridimensional da anatomia do paciente. Essa abordagem, facilitada pelo uso de software de planejamento assistido por computador, permite um planejamento mais preciso e individualizado (12) .…”
Section: Historicamenteunclassified
“…Portanto, qualquer lesão odontogênica nessa região pode ter impactos significativos na saúde bucal e na qualidade de vida do paciente (8,9) . (10,11,12) .…”
Section: Introductionunclassified